2017
DOI: 10.1001/jamapediatrics.2017.1333
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Nebulized Hypertonic Saline Treatment in Emergency Departments on the Hospitalization Rate for Acute Bronchiolitis

Abstract: for the Efficacy of 3% Hypertonic Saline in Acute Viral Bronchiolitis (GUERANDE) Study Group IMPORTANCE Acute bronchiolitis is the leading cause of hospitalization among infants. Previous studies, underpowered to examine hospital admission, have found a limited benefit of nebulized hypertonic saline (HS) treatment in the pediatric emergency department (ED).OBJECTIVE To examine whether HS nebulization treatment would decrease the hospital admission rate among infants with a first episode of acute bronchiolitis.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
66
0
3

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 50 publications
(71 citation statements)
references
References 25 publications
0
66
0
3
Order By: Relevance
“…Table shows the results of subgroup analyses. A significant effect of HS in reducing the risk of hospitalization was found only in the pooled analyses of trials in which HS was mixed with bronchodilators, multiple doses (≥3) were given, and risk of bias was low …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Table shows the results of subgroup analyses. A significant effect of HS in reducing the risk of hospitalization was found only in the pooled analyses of trials in which HS was mixed with bronchodilators, multiple doses (≥3) were given, and risk of bias was low …”
Section: Resultsmentioning
confidence: 98%
“…No serious adverse events (AEs) were reported. Three trials reported at least one event, and worsening of cough was the most frequently reported minor AEs which occurred in 6.6% of patients treated with HS and 0.8% of patients treated with NS …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Another scoring system, the modified Respiratory Index Score (RIS), was found to be a reasonable predictor of the need for hospital admission in a single‐center study in Singapore . A large multicenter clinical trial did not show any benefit of nebulized hypertonic saline for reduction of hospital admissions in acute bronchiolitics in an emergency department setting . In a review, Hancock et al pointed out the ongoing heterogeneity of definitions used for viral bronchiolitis in published literature, which continues to hamper comparisons among studies.…”
Section: Introductionmentioning
confidence: 99%
“…There is increasing evidence—based on new RCT studies and most recent meta‐analyses—that HS inhalations are not useful in bronchiolitis in infants . The multicenter SABRE study form UK compared 141 infants hospitalized for bronchiolitis at less than 12 months of age and treated with HS inhalations 6‐h, with 159 control infants treated with “minimal handling” standard care without any inhalations .…”
mentioning
confidence: 99%